Effect of Aloe vera Gel for Inducing Rooting of Stem Cuttings and Air layering of Plants. - Mirihagalla, M.K.P.N.; Fernando, K.M.C. (University of Jaffna, 2020)
Plant growth regulators (PGRs) are important to facilitate root formation and firm plant establishment hence used in vegetative propagation for many years. Farmers use natural alternative compounds to induce rooting of cuttings. The present study was conducted to identify the effect of Aloe vera gel on root formation of stem cuttings and air layering of plants. Three experiments were conducted to compare A. vera gel with commercially available PGR for root induction of semi hard wood cuttings(Citrus aurantifolia), softwood cuttings (Coleus spp.) and air layering plants (Syzygium jambos). Average root length, number of roots and root vigour were recorded as root traits. Effect of PGR and Aloe vera gel on root traits was not significantly different for C.aurantifolia and S.jambos. However, effect of PGR was significantly different on root traits compared to cuttings did not receive either A. vera gel or PGR. Therefore, synthetic PGRs can be replaced by A. vera gel, a natural alternative root inducing substance, for semi hardwood cuttings of C. aurantifolia and air layering of S. jambos but not for softwood cuttings of Coleus spp. These finding could be used in developing natural root inducing substance and resolving and reducing the risk of chemical toxicity in plants due to PGRs.
Keywords: Aloe vera gel; Air layering; Plantgrowth regulators; Rooting; Stem cutting